Perancangan Sistem Otomatis Berbasis PLC pada Mesin Injeksi Cetak Plastik Tipe Vertikal - Agus Purnomo; Adhes Gamayel; Mohamad Zaenudin (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2024)
The PLC System in Vertical Plastic Injection Molding Machine is an automated electrical system designed with sensor inputs controlled by a PLC Mitsubishi FX0s-20MR. It is supplemented with additional devices such as Proximity switches and Thermocouple PID-CX100. The research aims to analyze the heater temperature to control the movement of the injection piston for controlled movement, enhancing the efficiency of the molding injection process, and preventing operational errors that could affect the machine's condition, performance, and the molding results. From the experiments conducted, it was found that the settings producing specimens with near-perfect or perfect results were in experiments number 5 and 6. The injection time in these experiments was successfully adjusted using a timer setting in the PLC program, with an automatic injection time of 15 seconds. Based on these results, it can be concluded that the optimal settings for the molding process using PP material in this equipment are a temperature of 200-210°C, pressure of 4-5 bars, and injection time of 15 seconds.